P328Investigating the cause of transposition of great arteries. (15th July 2014) - Bada, WU; Miossec, MJ; Hussain, R; Goodship, J; Keavney, B
Abstract: Introduction: Congenital heart disease (CHD) is the most common congenital abnormality, affecting approximately 7 in 1, 000 live births. Transposition of the great arteries (TGA) is the most commonly diagnosed cyanotic heart defect in neonates. We propose that TGA has a genetic cause, likely to be de novo or in genes causing heterotaxy syndrome. Purpose: Exomes of 9 subjects diagnosed with TGA with no family history of CHD and their unaffected parents (trios) were subject to sequencing. The project aims were to: implement the exome bioinformatic analysis pipeline to identify de novo mutations (DNMs) and validate variants called by the pipeline. This is the first study investigating de novo changes in TGA patients. Methods: Bioinformatic pipeline was set up to analyse sequencing performed on Illumina GAIIX following exon capture. Programs used included Casava-Gerald after base calling, NovoAlign/BWA for alignment, SAMtools for variant calling. Integrated Genomics Viewer was used to inspect the variants. Polymerase chain reactions were performed prior to sending off for validation by Sanger sequencing. Results: Bioinformatic pipeline identified on average 188 DNMs per trio. 17 variants were chosen for validation. 1 trio had 2 de novo mutations: 1 nonsense in ZNF227 and 1 missense in PHLPP2. 1 trio had a de novo change in RBP5 gene. 1 trio had an inherited splice site change in RTTN, a candidate gene. Conclusions: The presence of de novo and inherited mutations suggests a complex polygenic cause of TGA.